Analysis of total phenolic content and antioxidant activity of mahogany seed infusion (Swietenia mahagoni (L.) Jacq.) - Pratiwi, Sindi; Emelda, Emelda; Kusumawardani, Nurul; Munir, Muhammad Abdurrahman; Azizah, Abibatul; Pothitirat, Werayut (Alma Ata University Press, 2024)
Background: The mahogany plant (Swietenia mahagoni) is a plant used in medicine. Mahogany seeds are also efficacious as antiseptics, antioxidants, and antimicrobials. This plant contains flavonoids, saponins, tannins, essential oils, alkaloids, and anthraquinones. The higher the phenolic content in a plant, the higher the antioxidant activity. According to previous studies, it was stated that the methanol extract of mahogany seeds has good antioxidant properties, and the phenolic compounds contained in mahogany seeds can be the main contributors to antioxidant activity.Objectives: This study aims to analyze the total phenolic content, measure the inhibition concentration 50% (IC50) and determine the antioxidant activity of mahogany (Swietenia mahagoni) seed infusion.Methods: This type of research is experimental which begins with extraction using the infusion method at a temperature of 900C for 15 minutes followed by measuring the total phenolic content by reacting the infusion preparation and the Gallic acid respectively with the Follin-ciocalteu reagent. The antioxidant activity test was carried out using the DPPH (ï¡,ï¡-diphenyl-ï¢-picrylhydrazyl) free radical scavenging method. Each absorbance was measured using UV-Vis Spectrophotometry. The phenolic test was measured by making a linear regression between concentration and absorbance, followed by calculating the total phenolic content. Meanwhile, the absorbance obtained for the antioxidant test was calculated by calculating the percent inhibition. The IC50 is determined by calculating the linear regression of the relationship between concentration and percent inhibition.Result: The results of the phenolic content were 2.531 ± 0.029 mg GAE/g, the IC50 value for gallic acid was 5.54 ppm, and for mahogany seed extract, the IC50 value was 47.04 ppm, which is a very strong antioxidant.Conclusion: This study concluded that the phenolic content of mahogany seed infusion extract contained phenolic compounds equivalent to 2.531 ± 0,029 mg GAE/g of gallic acid and that mahogany seed extract had very strong antioxidant activity.